Persistence of nematic liquid crystalline phase in a polyfluorene‐based organic semiconductor: A high pressure study. Issue 15 (5th June 2014) - Guha, Suchismita; Knaapila, Matti; Moghe, Dhanashree; Konôpková, Zuzana; Torkkeli, Mika; Fritsch, Martin; Scherf, Ullrich
ABSTRACT The role of high pressure on a low molecular weight nematic liquid crystalline organic semiconductor, ethyl‐hexyl substituted polyfluorene (PF2/6) is investigated using photoluminescence (PL), Raman scattering, and X‐ray scattering studies at pressures from 1 to 8 GPa. The PL and the Raman data under pressure are consistent with each other with no abrupt changes in the pressure coefficients of PL or Raman peaks. The PL energies redshift and broaden, consistent with both enhanced intra‐ and interchain interactions. The Raman peak positions yield pressure coefficients similar to other phenyl based π‐conjugated polymers. The broadening of a doublet peak in the 1135 cm−1 region indicates a more planar backbone conformation with increasing pressure. X‐ray scattering indicates that the torsion angle between adjacent repeats reduces with increasing pressure and reverts back with decompression. The intermolecular structure is weakly ordered (frozen nematic) and essentially maintained with increasing pressure, in contrast to a high molecular weight PF2/6. © 2014 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys. 2014, 52, 1014–1023